Nilai dan Hukum Islam Pemberian Sesajen Sebelum Akad Nikah (Kajian Atas adat Masyarakat Desa Sukoharjo Kecamatan Bancar Kabupaten Tuban) - Zamroni Ishaq Ishaq; Anik Pujayanti (JOSH: Journal of Sharia, 2022)
The Javanese people pay so much attention to marriage, that for matters of wedding day and reception or moving house, they also have to do the weton count and also provide offerings before the marriage contract is carried out, as the people of Sukoharjo do. Therefore, researchers are intrigued to find out what causes them to do this habit, the form of offerings, values, and Islamic law?. To obtain the required data, the researcher used several instruments including: interviews, observation, documentation. Interviews were conducted, among others, to those who have carried out the tradition, to religious leaders, community leaders, and members of the Sukoharjo village community. The conclusions resulting from this study include; First, the habits carried out by their ancestors before and the feeling of being haunted by a sense of worry about something bad that will happen to them if they don't do this habit. Second, there are two forms of offerings made by the community in Sukoharjo Village, Bancar District, Tuban Regency related to the wedding ceremony; 1) Sadaqah offerings that are not unlawful. 2) Deasel and Pawon offerings which are haraam.